(untitled) (Journal of the College of Basic Education, 2025)
Reverse osmosis (RO) desalination plants represent an effective solution to the growing scarcity of safe drinking water. This study investigates selected physical and chemical characteristics of tap water and RO-treated water in several desalination plants located in different regions of Baghdad, including both the Rusafa and Karkh districts. A total of 120 samples were collected: 60 samples of RO-treated water (30 from Rusafa and 30 from Karkh) and 60 tap water samples (30 from each side). Laboratory analyses were conducted to measure parameters such as temperature, pH, electrical conductivity, total dissolved solids (TDS), and salinity. The results indicated noticeable variations among the samples; however, most measured values were within the permissible limits established by Iraqi Standard No. 417 (2009), demonstrating the effectiveness of RO systems in enhancing water quality. Despite these positive findings, the study identified several operational challenges, including the need for regular membrane maintenance and improved technical training for plant personnel. Therefore, the study recommends strengthening monitoring and quality control measures, and implementing sustainable maintenance programs to ensure the consistent supply of safe, high-quality drinking water.